Analysis of Factors that Influence Students' Interest in Continuing Their Studies at Semarang University (S1 Management Studies) - Miftanudin, Arif Miftanudin; Ekawati, Yuniasih Ekawati; Souisa, Johanis Souisa; Cahya, Desy Cahyaningrum; Retno (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to empirically test student motivation, desire and aspirations for student interest. The problem faced by Semarang University is the increasing number of students interested in continuing to higher education. Population study This is a Prospective New Student at Semarang University. Samples used in study This is amounting to 100 respondents . In the study This use Purposive sampling and questionnaire techniques with measurement scale likert . Then the data is obtained researched using SPSS 25 which includes assumption testing classic , analysis multiple linear regression , testing hypothesis through the t test and f test, as well analysis coefficient determination (R2). Test result This show that all variable Independent that is Motivation , Will students , and influential ideals positive and significant towards Student Interests For continue College (Y). Based on mark coefficient determination 0.994 which means 99.4% at Semarang University is influenced by variables Motivation , Will students , and ideals while the rest amounting to 0.06% is influenced by other variables outside the model studied.